2013
DOI: 10.1016/j.jaut.2012.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-21 is associated with elevated pro-inflammatory cytokines in dominant-negative TGF-β receptor type II mouse

Abstract: Dominant negative TGF-β receptor II (dnTGF-βRII) mice spontaneously develop an autoimmune cholangitis resembling human primary biliary cirrhosis (PBC). Interestingly, the dominant negative TGF-β receptor is expressed by both CD4+ and CD8+ T cells and leads to greatly reduced (but not absent) TGF-β signaling resulting in T cell intrinsic cell mediated autoimmunity. However, the mechanisms of the T cell dysregulation remain unclear. Recently it has been shown that TGF-β signaling is intimately involved with miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 48 publications
1
67
0
Order By: Relevance
“…These results suggest that the overexpression of miR-21 could decrease the expression of TGF-β1 mRNA, which further down-regulates the frequency of circulating Treg cells and foxp3 mRNA levels [39]. In turn, the decrease in Treg cell frequency and the down-regulation of foxp3 result in less TGF-β1 secretion, suggesting an inhibition of the anti-inflammatory effect of Treg cells.…”
Section: Expression Levels Of Mir-21 Foxp3 Tgf-β1 and Smad7 In Pbmcmentioning
confidence: 85%
“…These results suggest that the overexpression of miR-21 could decrease the expression of TGF-β1 mRNA, which further down-regulates the frequency of circulating Treg cells and foxp3 mRNA levels [39]. In turn, the decrease in Treg cell frequency and the down-regulation of foxp3 result in less TGF-β1 secretion, suggesting an inhibition of the anti-inflammatory effect of Treg cells.…”
Section: Expression Levels Of Mir-21 Foxp3 Tgf-β1 and Smad7 In Pbmcmentioning
confidence: 85%
“…Nevertheless, it has been reported that suppression of miR-21 causes a reduction in the pro-inflammatory cytokine TNF-α and monocyte chemoattractant protein-1 in a mouse model of type 2 diabetes [38]. Another study revealed that overexpression of miR-21 resulted in up-regulation of TNF-α and interferon-γ in B6 T cells [39]. Therefore, these results indicate that miR-21 may play different roles in various types of cells and tissues in response to a variety of stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…These opposing actions are analogous to pressing the gas pedal while stepping on the brake; however, it takes days for the repressive miR-21 to build up in a cell before blocking translation (29)(30)(31). This provides a plausible mechanism for suppression of T-cell activation to limit the immune response.…”
Section: Predictions Of Transcription Factor Locations In Promoter Rementioning
confidence: 99%